Advanced cold patching materials (CPMs) for asphalt pavement pothole rehabilitation: State of the art. (15th September 2022) - Wang, Tao; Dra, Yasin Amara Sekou S.; Cai, Xiaopei; Cheng, Zhiqiang; Zhang, De; Lin, Yi; Yu, Huayang
Abstract: As one of the most common diseases of asphalt pavement, potholes can be defined as bowl-shaped cavities with steep edges of various sizes on the pavement surface. Currently, Cold Patching Materials (CPMs) have become a preferred choice for pothole repair on asphalt pavements in cold and wet weather, to timely restore pavement serviceability and improve traffic safety. However, the survival time of conventional CPMs is not satisfactory enough, while the advanced (probably more expensive) CPMs that can achieve longer repair longevity may be more cost-effective in the long term. The main objective of this paper is to review the state-of-the-art advanced CPMs for more effective pothole repair of asphalt pavement in adverse conditions, and the advanced CPMs with specially formulated binders and aggregates by far are categorized into three groups: 1) Durable CPMs through binder modification, synthetic binder and fiber reinforcement; 2) Sustainable CPMs considering the use of alternatives (e.g., renewable binder and recycled aggregate) to nonrenewable resources; 3) Less toxic CPMs considering the use of alternatives to toxic solvents or diluents. Finally, the challenges and opportunities for future studies on CPMs are also summarized, including the exploration of novel polymer binders, the application of recycled polymers in binder modification and the development of appropriate evaluation methods for CPMs. Highlights: The durability of CPMs is improved through binder modification, employment of novel synthetic binder and fiber reinforcement. Potential alternatives to nonrenewable resources are worth consideration for sustainability of CPMs. Less toxic or nontoxic diluents that can also achieve comparable performance were recommended for cutback asphalt CPMs.